1992
DOI: 10.1002/sca.4950140303
|View full text |Cite
|
Sign up to set email alerts
|

Chromatism and confocality in confocal microscopes

Abstract: In confocal microscopes, whenever a broadband light source is used, or when excitation and detection are performed at different wavelengths, for example in fluorescence, then the influence of microscope objective chromatism on the degree of confocality is very important. With poorly corrected objectives, depth of field will be increased and in the case of fluorescence the image may be lost altogether. Presented here are observations with truly achromatic reflecting objectives and with the same objectives modif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1994
1994
2006
2006

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 3 publications
0
7
0
Order By: Relevance
“…In multicolour microscopy several excitation wavelengths and emission bands are used. Therefore, the microscope objective chromatism influences both confocality (depth of field) and detection efficiency (Akinyemi et al, 1991;Majlof & Forsgren, 1993). Even the best achromatic and apochromatic objectives have residual chromatic aberration (Fricker & White, 1992).…”
Section: Microscope Objective Chromatismmentioning
confidence: 99%
“…In multicolour microscopy several excitation wavelengths and emission bands are used. Therefore, the microscope objective chromatism influences both confocality (depth of field) and detection efficiency (Akinyemi et al, 1991;Majlof & Forsgren, 1993). Even the best achromatic and apochromatic objectives have residual chromatic aberration (Fricker & White, 1992).…”
Section: Microscope Objective Chromatismmentioning
confidence: 99%
“…The best axial resolutions are achieved with the highest numerical aperture lenses but generally, the higher the numerical aperture, the shorter the working distance of the lens, thereby lessening the depth to which such a lens can probe into tissue. Reflective lens objectives, which use curved mirrors as lenses, may provide a solution to this9.…”
Section: Limitationsmentioning
confidence: 99%
“…CSLM is particularly sensitive to chromatic aberrations, as light waves of different colours are focused to different depths within the tissue9. This can be a problem in work employing white light or laser excitation of multiple fluorophores which need to be imaged simultaneously but which fluoresce with, and are excited by, different wavelengths3.…”
Section: Limitationsmentioning
confidence: 99%
“…We checked that wavelength-dependent distortions were small compared with the optical resolution for objects close to the coverslip. The possible chromatic aberrations (Akinyemi et al, 1992) are considerably reduced by using plan apochromatic objective lenses, provided that for an oil-immersion lens imaging an aqueous specimen, the plane of focus is adjacent to the coverslip (Keller, 1995). Actual measurements provided by Leica Lasertechnik indicate that the relative axial shifts between 488 and 568 nm lines are never greater than 50 nm using 100 1 .…”
Section: Configuration Of the Confocal Laser Scanning Microscopementioning
confidence: 99%
“…Global correlation coefficients have been explored to estimate the degree of correspondence between two related fluorescence micrographs (Manders et al, 1992(Manders et al, , 1993. In addition, several authors have identified fluorescence cross-talk and image registration defects due to chromatic aberrations or misalignment of confocal optics as fundamental problems in multifluorescence acquisitions (Akinyemi et al, 1992;Sandison et al, 1995;White et al, 1996). A judicious choice of fluorophores, laser types, objective lenses, fluorescence filter sets, detection pinhole settings and photon detectors often reduces these limitations (Mossberg & Ericsson, 1990;Sheppard et al, 1992;Brelje et al, 1993;Keller, 1995;Tsien & Waggoner, 1995), which can further be compensated for by digital image processing (Carlsson & Mossberg, 1992;Brelje et al, 1993).…”
Section: Introductionmentioning
confidence: 99%